Observer-Based Fully Distributed Containment Control for MASs Subject to DoS Attacks - Ma, Yong-Sheng; Che, Wei-Wei; Deng, Chao; Wu, Zheng-Guang (IEEE transactions on systems, man, and cybernetics. Systems, 2023)
The problem of the observer-based fully distributed containment control for multiagent systems (MASs) subject to denial-of-service (DoS) attacks is investigated in this article. First, a switched fully distributed control framework is established for a class of DoS attacks constrained by the attack duration. Then, a novel attack-resilient control scheme is developed to accomplish the containment control task. The major advantages of the devised control scheme are that any information of the whole network topology structure is not involved and only the information from neighbor agents is used. What is more, a novel observer-based attack compensator is devised to resist DoS attacks. Finally, a practical example of the mobile robot system is presented to testify the validity of the designed control scheme by a comparison.